PELATIHAN PEMBUATAN LAPORAN KEUANGAN SEDERHANA UMKM MENGGUNAKAN MS. EXCEL TAHUN 2010 DI KECAMATAN PARON DAN KECAMATAN PITU - Iin Maulidah Khasanah, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Micro, small and medium enterprises commonly referred to as MSMEs are one type of business or business entity that really plays a role and contributes to the economy. MSMEs must now improve the recording of good financial statements. Recording financial statements is one of the important stages in a business. Financial reports are useful for presenting financial information which is certainly used by internal and external parties involved in business operations. But in reality, there are still many MSME players who have not compiled company financial reports for various reasons. On this occasion, I would like to train MSME players how to make or summarize simple financial reports using Ms. Excel that are easily understood by business owners, especially in Paron and Pitu sub-districts. I see that MSME players here still use financial reports manually and do not have good and accurate financial reports according to financial accounting standards, where company owners have not separated financial reports between capital, income, expenses or for personal gain. Based on these problems and observations, I have conducted awareness-raising activities related to the preparation of simple financial reports for ease of implementation by MSMEs in Paron and Pitu sub-districts